The effect of using competition and inclusion methods in improving some technical skills in football for middle school students (Journal of the College of Basic Education, 2022)
The importance of the research lies in studying the effect of using some teaching methods, including the competitive method and the method of embedding in learning basic football skills for students, to address the research problem represented in the presence of a clear weakness in learning basic football skills among middle school students according to the methods used and the lack of use of modern and diverse methods which That would work to learn and develop the basic skills well, while the objectives of the research were to identify the impact and effectiveness of using the competitive method and the method of embedding in learning and developing the most important basic skills in football. The researcher used the experimental method for its suitability to the variables and problem of the research studied. The study community consisted of second-grade intermediate students in middle and secondary schools in the Maimouna Education Directorate sector affiliated to the Maysan Education Directorate for the academic year 2021 AD - 2022 AD. And the sample of the application was from the students of the second intermediate grade in Sheikh Al-Tusi High School, and the skill tests that fit the skill research variables were determined and applied to the application sample for the purpose of obtaining the required data to be collected and analyzed for the purpose of arriving at the results through which the most important conclusions and recommendations that the researcher recommends to use for the purpose of Achieving the educational goals as required.